Nanocarriers as Administration Systems of Natural Products - Solís-Cruz, Guadalupe Y.; Pérez-López, Luis A.; Alvarez-Roman, Rocio; Rivas-Galindo, Verónica M.; Silva-Mares, David A.; Ibarra-Rivera, Tannya R. (Current Topics in Medicinal Chemistry, 2021)
Natural products are an important source of bioactive molecules. However, the development of biological applications based on these compounds is hindered by intrinsic problems in their solubility, volatility, degradation, and bioavailability. Nanocarriers as drug administration systems promise to overcome these limitations by providing controlled and directed delivery. This review aims to present 1) the most frequently used nanocarriers as natural product administration systems, based on the progress of controlled and directed release, and 2) the challenges associated with the use of nanocarriers as therapeutic agents.
Keywords: Nanostructures